2023
DOI: 10.47297/wspchrmwsp2040-800501.20231402
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paternalistic Leadership Styles on Employee Engagement in the Pharmaceutical Distribution Industry: The Mediating Role of Psychological Capital

Li Chen,
Jiangxin Liu,
Weifeng Qiu
et al.

Abstract: The COVID-19 pandemic has brought great challenges to health workers. In view of the impact of paternalistic leadership styles on employee psychology and engagement, this study aims to explore the relationship between paternalistic leadership styles and employee engagement during the COVID-19 pandemic and the mediating role of psychological capital. Paternalistic Leadership Questionnaire (PLQ), Psychological Capital Questionnaire (PCQ) and Employee Engagement Scale (EES) were used to investigate 557 employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Employees who experience higher feelings of accountability believe that their action will be closely watched and scrutinized by a salient audience. 27 , 37 , 38 Researchers have suggested that there exist individual differences in how felt accountability influences cognitions and behaviors in the workplace. 37 , 39 We argue that several elements of narcissism potentially trigger feelings of accountability when organizational wrongdoing is discovered.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Employees who experience higher feelings of accountability believe that their action will be closely watched and scrutinized by a salient audience. 27 , 37 , 38 Researchers have suggested that there exist individual differences in how felt accountability influences cognitions and behaviors in the workplace. 37 , 39 We argue that several elements of narcissism potentially trigger feelings of accountability when organizational wrongdoing is discovered.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The actors believe that they will be required to give a salient audience explanation. 27 Prior research has shown that narcissistic CEOs are more likely to forgo irresponsible behaviors which can easily lead to criticism from stakeholders and therefore engage in more corporate social responsibility. 32 Narcissistic individuals prefer to stand out from the crowd and get attention and recognition.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations